2005
DOI: 10.1111/j.1745-3933.2005.00025.x
|View full text |Cite
|
Sign up to set email alerts
|

Period—colour and amplitude-colour relations for MACHO project Large Magellanic Cloud RR Lyrae stars

Abstract: In this Letter, we analyse period–colour and amplitude–colour relations at minimum, mean and maximum V‐band light for 6391 RRab stars in the Large Magellanic Cloud obtained by the MACHO project. Specifically, we find that colour and amplitude are nearly independent of period at minimum light, but that there exists a definite relation between period and colour and amplitude and colour at maximum light. These two properties are consistent with earlier work suggesting that these observed properties are, at least … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 12 publications
2
18
1
Order By: Relevance
“…In summary, our study reveals that the structural form of PC and AC relations at maximum and minimum lights for RR Lyraes are much more complicated than previously thought (Kanbur & Fernando 2005;Bhardwaj et al 2014). They can be expressed as either a flat, a linear, or a quadratic relation in different colors.…”
Section: Discussionmentioning
confidence: 60%
See 3 more Smart Citations
“…In summary, our study reveals that the structural form of PC and AC relations at maximum and minimum lights for RR Lyraes are much more complicated than previously thought (Kanbur & Fernando 2005;Bhardwaj et al 2014). They can be expressed as either a flat, a linear, or a quadratic relation in different colors.…”
Section: Discussionmentioning
confidence: 60%
“…The observed PC relations were also compared to the synthetic colors in Figure 5. 3.1. The PC Relations at Maximum Light Kanbur & Fernando (2005) and Bhardwaj et al (2014) found a significant non-zero and positive slope for the PC relation at maximum light in the (V − R) MACHO and (V − I) colors, respectively. In the left panel of Figure 3 we plotted the PC relations at maximum light for RRab and RRc stars: these display a variety of behavior.…”
Section: Methodsmentioning
confidence: 95%
See 2 more Smart Citations
“…Yet another explanation proposes that the Oosterhoff gap is based on the structure of the envelope in these pulsating stars. Kanbur & Fernando (2005) have suggested that understanding the physics behind the Oosterhoff Effect requires a detailed investigation of the interplay between the photosphere and the hydrogen ionization front in an RR Lyrae variable. Because these features are not co-moving in a pulsating atmosphere, their interaction with each other can affect the period-color relation of RR Lyraes, possibly accounting for the behavior of their mean periods as a function of metallicity and, therefore, helping to explain the Oosterhoff Effect.…”
Section: Rr Lyrae Starsmentioning
confidence: 99%